Efficient recovery of Fe (III) from dechroming sludge with a novel combined process of acidic leaching and on-line adsorption - Chengbin Zhong; Junxia Yu; Boxi Wu; Qingbiao Zhao; Kairui Zhou; Jia Wang; Li Guo; Ruan Chi; Zhen Luo; Xiang Zhang (Journal of Environmental Chemical Engineering, 2026)

Efficient recovery of chromium from electroplating sludge by a two-step roasting process: Mechanisms and kinetics - Chengbin Zhong; Junxia Yu; Boxi Wu; Jia Wang; Li Guo; Ruan Chi; Zhen Luo; YingYing Liu (Minerals Engineering, 2026)

Oil Film Segmentation Method Using Marine Radar Based on Feature Fusion and Artificial Bee Colony Algorithm - Jin Xu; Bo Xu; Xiaoguang Mou; Boxi Yao; Zekun Guo; Xiang Wang; Yuanyuan Huang; Sihan Qian; Min Cheng; Peng Liu; Jianning Wu (Journal of Marine Science and Engineering, 2025)
In the wake of the continuous development of the international strategic petroleum reserve system, the tonnage and quantity of oil tankers have been increasing. This trend has driven the expansion of offshore oil exploration and transportation, resulting in frequent incidents of ship oil spills. Catastrophic impacts have been exerted on the marine environment by these accidents, posing a serious threat to economic development and ecological security. Therefore, there is an urgent need for efficient and reliable methods to detect oil spills in a timely manner and minimize potential losses as much as possible. In response to this challenge, a marine radar oil film segmentation method based on feature fusion and the artificial bee colony (ABC) algorithm is proposed in this study. Initially, the raw experimental data are preprocessed to obtain denoised radar images. Subsequently, grayscale adjustment and local contrast enhancement operations are carried out on the denoised images. Next, the gray level co-occurrence matrix (GLCM) features and Tamura features are extracted from the locally contrast-enhanced images. Then, the generalized least squares (GLS) method is employed to fuse the extracted texture features, yielding a new feature fusion map. Afterwards, the optimal processing threshold is determined to obtain effective wave regions by using the bimodal graph direct method. Finally, the ABC algorithm is utilized to segment the oil films. This method can provide data support for oil spill detection in marine radar images.

Unraveling dynamics and interactions of core microorganisms in the biodegradation of keratin-based feather wastes - Boxi Wang; Yuan Chen; Jin Chuan Wu; Qingxin Li (Journal of Environmental Management, 2024)

Long-term hourly air quality data bridging of neighboring sites using automated machine learning: A case study in the Greater Bay area of China - Boxi Wu; Cheng Wu; Yuchen Ye; Chenglei Pei; Tao Deng; Yong Jie Li; Xingcheng Lu; Lei Wang; Bin Hu; Mei Li; Dui Wu (Atmospheric Environment, 2024)